Characterization of the genuine type 2 chromatic acclimation in the two Geminocystis cyanobacteria - Hirose, Yuu; Misawa, Naomi; Yonekawa, Chinatsu; Nagao, Nobuyoshi; Watanabe, Mai; Ikeuchi, Masahiko; Eki, Toshihiko (DNA research, 2017)
Certain cyanobacteria can adjust the wavelengths of light they absorb by remodeling their photosynthetic antenna complex phycobilisome via a process called chromatic acclimation (CA). Although several types of CA have been reported, the diversity of the molecular mechanisms of CA among the cyanobacteria phylum is not fully understood. Here, we characterized the molecular process of CA of Geminocystis sp. strains National Institute of Environmental Studies (NIES)-3708 and NIES-3709. Absorption and fluorescence spectroscopy revealed that both strains dramatically alter their phycoerythrin content in response to green and red light. Whole-genome comparison revealed that the two strains share the typical phycobilisome structure consisting of a central core and peripheral rods, but they differ in the number of rod linkers of phycoerythrin and thus have differing capacity for phycoerythrin accumulation. RNA sequencing analysis suggested that the length of phycoerythrin rods in each phycobilisome is strictly regulated by the green light and red light-sensing CcaS/R system, whereas the total number of phycobilisomes is governed by the excitation-balancing system between phycobilisomes and photosystems. We reclassify the conventional CA types based on the genome information and designate CA of the two strains as genuine type 2, where components of phycoerythrin, but not rod-membrane linker of phycocyanin, are regulated by the CcaS/R system.